(untitled) (Journal of Parents and Teachers, 1996)
The acquisition of reading and writing depends on language development and brain maturity, especially in the frontal lobe. Visual-motor coordination and phonological knowledge are fundamental for learning. It is recommended to prioritize vocabulary and play activities in the teaching of written language.